Microcatheter Crossing of Radial Artery Loops and Tortuosities: New Ideas in Reducing Trans Radial Approach Crossover - Vasilev, Ivan; Spiroski, Igor M.; Kostov, Jorgo; Jovkovski, Aleksandar; Zafirovska Biljana; Taravari, Hajber; Kedev, Sashko (Scientific Foundation Spiroski (publications), 2021)
BACKGROUND: Transradial access is currently the default access site for percutaneous cardiovascular interventions. Radial artery (RA) anomalies present a significant challenge in radial access success. RA 360-degree loops are an uncommon, but quite challenging vascular anomaly even for the most experienced radial operators.CASE REPORT: We report on two cases of patients with complex RA loops referred for PCI through radial approach in a high-volume radial center. Pre-procedural RA angiography was performed in both cases identifying a 360-degree RA loop in the proximal part of the RA below the entrance into the brachial artery. In both cases, we present a novel “Microcatheter crossing” technique of the complex RA loop as a new strategy in overcoming even the most difficult radial adversary. After identifying the loop a hydrophilic wire 0.014 inch was used to cross the loop and extend it in the upper arm. Then a microcatheter ASAHI corsair (Asahi Intecc USA, Inc.) was advanced through the loop without difficulty. The microcatheter is advanced through the wire until middle of the upper arm. Hydrophilic wire is then exchanged with High Torque Iron man guide wire (Abbott Vascular). Again, the wire is advanced in the upper arm. Microcatheter is then removed and 5F catheter JR 4.0 or similar is advanced gently through the iron man wire with a clockwise rotation through the loop. Then, wire and catheter are pulled back to straighten the loop. The percutaneous angiography procedure was performed successfully in both cases.CONCLUSION: Both patients were discharged without registered bleeding complications from place of puncture. They both reported slight pain during the beginning of the procedure in the arm of puncture, but without additional problems after the procedure.
Keywords: Transradial approach; Radial artery loop; Microcatheter